Contribution of Tailoring Business in Meeting Family Economic Needs from an Islamic Economic Perspective (Study on Tailors in Sukakarya District, Musi Rawas Regency) - Fidiyah Rayina Sugesti; Supardi Mursalin; Romi Adetio Setiawa (UNIVED Press, 2024)
This study aims to find out how the sewing business in Sukakarya sub-district contributes to household needs, the inhibiting and driving factors in business, and the description of the sharia economy on the sewing business transaction system in Sukakarya Sub-district. This research was conducted using a qualitative approach with data collection techniques interviewing tailors and consumers. From the results of this study it was found that the sewing profession is a business that contributes to improving the economy in the Sukakarya sub-district, but customer complaints are still often found regarding unsatisfactory sewing results and service. For this reason, the researchers suggest that the government take part in providing sewing training to improve the quality of sewing entrepreneurs in Musi Rawas, especially in Sukakarya sub-district.